Intrinsically Stretchable Organic Solar Cells with Simultaneously Improved Mechanical Robustness and Morphological Stability Enabled by a Universal Crosslinking Strategy. Issue 26 (31st May 2022) - Wang, Zhenye; Zhang, Di; Xu, Meichen; Liu, Junfeng; He, Jiayi; Yang, Lvpeng; Li, Zhilin; Gao, Yerun; Shao, Ming
Abstract: Developing intrinsically stretchable organic solar cells (OSCs) with excellent mechanical robustness and long‐term operation stability is highly demanded for practical applications. Here, the representative PM6/Y6 active layer film, crosslinked by a photo‐crosslinkable small molecule 2, 6‐bis(4‐azidobenzylidene)cyclohexanone (BAC) containing azide groups, exhibits a significantly enhanced stretchability of 18% and toughness of 6.94 MJ m −3, compared to non‐crosslinked film (stretchability of 4.5% and toughness of 0.75 MJ m −3 ). It is found that controlling the crosslinking density, including crosslinker concentration and crosslinking time, plays a vital impact on the stretchability and mechanical toughness of active layer film. The resulting intrinsically stretchable OSCs achieve a high power conversion efficiency (PCE) of 13.4% and retain 80% of its performance even under the large strain of 20%. To date, this is the highest PCE for intrinsically stretchable OSCs based on small molecular acceptors. Moreover, crosslinking of active layer film suppresses the crystallization of PM6 polymer chains and avoids the excessive aggregation of small molecular acceptors under thermal heating or light illumination, leading to a stabilized film morphology and significantly improved device stability. Overall, these results provide a universal strategy to simultaneously enhance the mechanical properties and stability of OSCs without sacrificing their photovoltaic performance. Abstract : A universal crosslinking strategy simultaneously enhances the mechanical robustness and stability of intrinsically stretchable organic solar cells (OSCs). The photo crosslinked active layer film exhibits the enhanced stretchability of 18% and toughness of 6.94 MJ m −3 . The OSCs also show significantly improved device stability with the stabilized film morphology stem from crosslinking.